Differences in the direction of effort adaptation between mountain bikers and road cyclists - Zaton, M.; Dabrowski, D. (Human Movement, 2013)
Purpose. Different forms of cycling require the use of different abilities and skills. The aim of this paper was to attempt to identify differences in the directions and dynamics of the body`s adaption to training in road (ROAD) and mountain (MTB) cyclists. Methods. Research was performed on a group of competitive road (n = 25) and mountain (n = 25) cyclists, mean age 16.96 ± 0.78 years presenting maximal oxygen uptake values of 4.45 ± 0.47 L/min-1. Body composition and physiological and biochemical parameters at rest, during exercise, and during restitution (cool down) were determined. Exercise was performed on a cycle ergometer in the form of a progressive load test. Analysis of the results included cluster analysis and basic statistical methods. Results. Cluster analysis indicated that the amount of work performed during the progressive load test was a universal indicator of physical fitness. The level of base excess (BE) in the 3rd min of restitution had a large influence on the remaining parameters in both groups. Training adaptation in MTB were manifested through increased values of maximum heart rate, blood oxygen saturation, oxygen partial pressure, and lactate and BE levels in the blood, as well as a reduction in blood pH and body mass. Conversely, in ROAD, adaptation to effort was evidenced by increased maximum values of oxygen uptake, minute ventilation, cardiac output and the rate of carbon dioxide elimination as well as an increase in hematocrit count and lean body mass. Conclusions. Adaptation to training by road cyclists is primarily evident in the development of aerobic capacity. Mountain biking induces adaptive changes in the development of anaerobic capacity by increasing the buffer capacity of the blood and muscles, as well as the development of the oxygen transportation system.